Dynamics of supercavitating vehicles with cone cavitators - Володимир Семененко; Володимир Мороз; Віктор Кочін; Олена Наумова (Mechanics and Advanced Technologies, 2022)
The work is devoted to theoretical and experimental investigations of dynamics of high-speed underwater supercavitating vehicles with cone cavitators. The cone cavitators are considered as operating controls of the supercavitating vehicle motion. The mathematical model of a “slender” unsteady cavity based on the G.V.Logvinovich principle of independence of the cavity section expansion is used. Experimental studies of the rotary cone cavitators were carried out at the high-speed experimental tank of the Institute of Hydromechanics of the NAS of Ukraine. Based on test results, the approximate dependences of both the drag coefficient and the lift coefficient of an inclined cone cavitator on the rotary angle in a wide range of cone angles are proposed. The range of cone angles is determined when the cone cavitators are the more effective operating controls in comparison with equivalent disk cavitator. With the help of computer simulation, a number of problems of dynamics of the supercavitating vehicle with cone cavitators were investigated: balancing the vehicle, the motion stabilization, maneuvering the vehicle, the cavity control. For the first time, experimental verification of the mathematical model of the supercavitating vehicle dynamics “as a whole” was performed by testing the model with cone cavitators and cavity-piercing fins with a degree of freedom in pitch.